PERENCANAAN FONDASI TIANG BOR PADA TANAH LANAU UNTUK GEDUNG APARTEMEN 20 LANTAI - Tati Noviati (Asosiasi Dosen Muda Indonesia, 2023)
Foundation is the part of the construction that transmits the load of the superstructure supported by the foundation with its own weight into the soil and rock that lies below it. The purpose of bored pile foundation planning is to design the dimensions of the foundation in the apartment building, calculate the axial and lateral bearing capacity, calculate settlement, calculate the reinforcement used and calculate the cost required for the construction of the bored pile foundation. The bored pile foundation in the apartment building used a circular foundation with a diameter of 0,5 meters which has a depth of 21 meters and located on sandy soil. The axial end bearing capacity of the bored pile uses the Reese & Wright method with a calculated value of 70,450 tons and the ultimate pile bearing capacity of 451,766 tons. Lateral bearing capacity of a single pile using the Evans and Duncan method is 16,359 tons and the maximum lateral bearing capacity of the group is 36,809 tons and the maximum deflection value is 1,419 mm. The bored pile foundation based on the calculation results refers to SNI 2847:2013 concerning Requirements for Structural Concrete for Buildings, for longitudinal reinforcement using 7D19 reinforcement and for spiral reinforcement using D16-40 reinforcement. The budget plan for the foundation and pile cap is Rp. 10.704.000.000.